1981
DOI: 10.1111/j.1476-5381.1981.tb09978.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Mechanical Activity of the Isolated Lower Urinary Tract of the Guinea‐pig

Abstract: 1 Strips of urethra taken from guinea-pigs contracted in response to acetylcholine, noradrenaline (via a-adrenoceptors) and 5-hydroxytryptamine, and were relaxed by adenosine triphosphate (ATP) if the tone was raised. Isoprenaline produced relaxation of bladder strips (via Padrenoceptors) whereas ATP caused contraction. 2 Atropine completely blocked all responses to acetylcholine; quinidine failed to block ATP responses selectively; methysergide blocked responses of the urethra but not the bladder to 5-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 13 publications
7
49
0
Order By: Relevance
“…Previous studies have documented the ability of serotonin to contract strips of urinary bladder obtained from dogs, 7,8 cats, 9 rabbits, 10 guinea pigs, 11 and humans. 12 We found that the contractile response to 5-HT was slightly but not significantly reduced in the rat bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the ability of serotonin to contract strips of urinary bladder obtained from dogs, 7,8 cats, 9 rabbits, 10 guinea pigs, 11 and humans. 12 We found that the contractile response to 5-HT was slightly but not significantly reduced in the rat bladder.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent paper has claimed that the excitatory effect of ATP on rabbit urethral smooth muscle is mediated by activation of P2Y receptors on ICCs, which act as pacemakers [85]. Bursts of spikes in the urethra were initiated by NA or ACh, but inhibited by ATP [124], perhaps after breaking down to adenosine. In the pre-contracted proximal urethra of the hamster, NANC nerve stimulation and exogenous ATP were also shown to produce relaxations, which were attenuated by suramin and Reactive Blue 2, and to a lesser extent by 8-PT, but not by PPADS.…”
Section: Urethramentioning
confidence: 99%
“…It is interesting that ATP has been claimed to be an inhibitory neurotransmitter to the guinea-pig urinary bladder neck [294]. When the tone of the urethra is raised, ATP caused relaxation, but if the tone of the urethra is low, high concentrations of ATP can cause contraction [124,169,351,553]. A more recent paper has claimed that the excitatory effect of ATP on rabbit urethral smooth muscle is mediated by activation of P2Y receptors on ICCs, which act as pacemakers [85].…”
Section: Urethramentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical activity occurs in bursts of APs superimposed on a slower rhythmic oscillation of membrane potential, and can be initiated by autonomic transmitters (Callahan and Creed, 1981). Both L-type and T-type Ca 2+ -currents have been recorded in isolated myocytes.…”
Section: Muscles Of the Urethramentioning
confidence: 99%